Automatic Configuration Sharing in Peer-to-Peer IoT Networks - Implementation and Evaluation of Automatic Configuration Sharing as a Linux Kernel Module - Nilsson, William; Wetter, Erik (My University, 2024)
Given that Internet of Things (IoT) devices are becoming more popular in the industry, faster ways of configuring these IoT devices need to be explored. This thesis was carried out in collaboration with Combitech AB to explore a new and automatic way of configuring IoT devices using Peer-To-Peer (P2P) networks and Linux Kernel Modules (LKMs). The resulting algorithm uses knowledge-sharing to distribute a configuration efficiently between homogeneous devices in the same P2P network. Tests on both physical and virtual devices show that the algorithm not only reduces the configuration times of new devices but also does so in a lightweight manner.
Keywords: Computer Science; Engineering; Embedded Linux; Kernel Module; Automatic Configuration; Industry; IoT; IIoT; P2P